2020
DOI: 10.1002/acm2.13058
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric and mechanical equivalency of Varian TrueBeam linear accelerators

Abstract: To investigate and improve the level of equivalency of Varian TrueBeam linear accelerators (linacs) in energy-, dosimetric leaf gap-(DLG) and jaw calibration. Methods: Eight linacs with four photon energies: 6 MV, 6 MV FFF, 10 MV FFF, and 15 MV, and three electron energies (on two linacs): 6, 9, and 12 MeV were commisioned and beam-matched. Initially, symmetry of lateral profiles was calibrated for maximum field size. Energy-matching was then performed for photons by adjusting diagonal profiles at maximum fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…Second, some studies have confirmed that the locally acquired beam data are either equivalent within 1% to that provided by the manufacturer [ 6 , 7 ] or to beam data for linacs of the same model [ 8 , 9 ]. Glide-Hurst et al [ 6 ] reported excellent agreement between five Varian TrueBeam data from three institutions.…”
Section: Opening Statement – Yousif Yousifmentioning
confidence: 95%
“…Second, some studies have confirmed that the locally acquired beam data are either equivalent within 1% to that provided by the manufacturer [ 6 , 7 ] or to beam data for linacs of the same model [ 8 , 9 ]. Glide-Hurst et al [ 6 ] reported excellent agreement between five Varian TrueBeam data from three institutions.…”
Section: Opening Statement – Yousif Yousifmentioning
confidence: 95%
“…The ability to match linacs at a level sufficient for routine treatments and PSQA has been assessed in several studies 1–8 . Initial investigations focus on the ability to achieve a high level of matching between characteristics of the linac output, such as beam profiles, depth dose curves, and output factors 1,2,4 .…”
Section: Introductionmentioning
confidence: 99%
“…Initial investigations focus on the ability to achieve a high level of matching between characteristics of the linac output, such as beam profiles, depth dose curves, and output factors 1,2,4 . Further investigations consider the resultant similarity within composite dose deliveries for volumetric‐modulated arc therapy (VMAT) or intensity‐modulated radiotherapy (IMRT) 3,5,8 . More recently investigations have begun to consider the possibility of linac matching at the level required for stereotactic radiotherapy 6,7 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 Linac beam‐matching process is also elaborated on in the literature for three‐dimensional conformal radiation therapy (3DCRT) and intensity‐modulated radiation therapy (IMRT) for the ease of patient transferability. 6 , 9 , 10 , 11 …”
Section: Introductionmentioning
confidence: 99%